Klasifikasi Tingkat Kerusakan Sektor Pasca Bencana Alam Menggunakan Metode MULTIMOORA Berbasis Web - Aniss Fatul Fu'adah; Agung Teguh Wibowo Almais; A’la Syauqi (JISKA (Jurnal Informatika Sunan Kalijaga), 2023)
During 2020-2021, 10,152 disasters occurred in Indonesia, significantly impacting the affected sectors. The recovery of these sectors needs to be done as quickly as possible to maintain human survival. This study aims to analyze the factors that affect sector damage after natural disasters in Indonesia and measure the classification accuracy. The data used in this research is data from the Regional Disaster Management Agency of Malang City in 2020. This study developed a web-based Decision Support System (DSS) using The Multiplicative Form Integrated MOORA (MULTIMOORA) method. This method is the result of the development of the MOORA method by adding a complete multiplication form to the MOORA method. In this study, the MULTIMOORA method was used to classify the level of damage to sectors after natural disasters. The results showed that using the MULTIMOORA method in this DSS resulted in an accuracy rate of 84% and was included in the good enough category.